2019
DOI: 10.1111/bcp.13923
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in adverse drug reactions reported to the National Pharmacovigilance Centre in the Netherlands: An explorative observational study

Abstract: Aims We aimed to assess and characterize sex differences in adverse drug reactions (ADRs) reported to the national pharmacovigilance centre in the Netherlands while considering differences in drug use. Methods ADRs spontaneously reported by healthcare professionals and patients to the Netherlands pharmacovigilance centre Lareb were used. Drug–ADR combinations reported at least 10 times between 2003–2016 for drugs used by ≥10,000 persons in that period were included. Data about the number of drug users was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
80
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 47 publications
14
80
2
3
Order By: Relevance
“…The reduction of sex differences in ADR reporting over time was accompanied by a lower dose of metformin among women at later stages after initiation. Previous studies indicate that women more often report an ADR than men for drugs in general [15][16][17][18], as well as for metformin specifically [5,19]. The current study adds to this knowledge that sex differences in metformin-associated ADRs are particularly shown at early stages after initiation.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The reduction of sex differences in ADR reporting over time was accompanied by a lower dose of metformin among women at later stages after initiation. Previous studies indicate that women more often report an ADR than men for drugs in general [15][16][17][18], as well as for metformin specifically [5,19]. The current study adds to this knowledge that sex differences in metformin-associated ADRs are particularly shown at early stages after initiation.…”
Section: Discussionsupporting
confidence: 50%
“…A previous study showed that ADRs experienced by people with diabetes can be transient or fluctuating over time [22] but it is not clear whether this differs between men and women. This could in part be a gender-related factor, since social, behavioral, and cultural differences between men and women may influence the experience and reporting of ADRs [15,23,24]. Women and men have different risk perceptions [25] and it has been shown that women more often read patient information leaflets than men [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the study also found differences in the drugs which were cited between the genders, particularly for endocrine, anti-infective and cardiovascular medicines. Differences in drugs and reported symptoms between the sexes have previously been shown in large-scale studies [27,28]. In addition, females were more likely to report serious reactions and to include more reaction terms in reports than males.…”
Section: Discussionmentioning
confidence: 67%
“…A "possibly relevant" sex difference was identified in 15% of the drug-ADR combinations after accounting for differences in medication use; the risk was higher for women than men in 89% of cases. 9 If personalized medicine is to become a reality, it is critical to understand not only interindividual genetic differences, but also underlying F I G U R E 1 Volcano plot of adverse drug event signals. In the volcano plot of ADE signals, the signal detection result shows the magnitude (log2 reporting odds ratio [ROR], x-axis) and significance (−log10 adjusted P value, y-axis) for sexdrug-event combinations associations of specific drugs.…”
Section: The Us Food and Drug Administration Adverse Event Reportingmentioning
confidence: 99%